BEING A MAN OR WOMAN:A GENDER ANALYSIS OF THE NOVEL MIDDLESEXBY JEFFREY EUGENIDES - Vebyanti, - (2009)
This research paper is entitled "Being a Man or Woman: a Gender Analysis on the Novel Middlesex by Jeffrey Euginides". This research focuses on the main character, a hermaphrodite, and uses gender theory by Judith Butler as the framework of the research. The aims of this research are to find out the factors influencing the change of gender and the taking and resisting of the new gender identity. The data are collected by highlighting the texts which show the textual evidence that related to the research questions. From the findings, the factors influencing the change of gender are sexual secondary characteristics development, sexual orientation, self-acceptance and family. Meanwhile, the taking of the new gender identity attitudes are by changing physical appearance, running away from the family in order not to change into a "normal" girl, being the guardian for his father funeral which is always done by man, and being a brother for his elder brother. The resisting of the new gender identity attitudes are always being a daughter for his mother, and performing in his previous gender unconsciously. From gender theory perspective that is offered by Judith Butler, it is found that gender is a performative act; it is a repetition of acts, behaviors, manners that heads to the two binary of gender, masculine and feminine that is accepted by the society. For a hermaphrodite, s/he has no choice but to choose one of genders in order to function in the society.